“Emotional intelligence and job satisfaction among staffs at Putra Specialist Hospital Melaka” / Abidah Suib - Suib, Abidah (Faculty of Business and Management, 2010)
This study seeks to investigate the emotional intelligence and job satisfaction among the staff at Putra Specialist Hospital Melaka. The objectives of the study were to examine the level of emotional intelligence as well as the job satisfaction among the staffs. Besides that, it also implements to know the relationship between emotional intelligence and job satisfaction. The literature suggests that employee skills in general and emotional intelligence in particular, play a significant role in the success of completing their goals in the workplace and hence perceived greater job satisfaction. Participants were 100 staffs include both nursing and non-nursing who completed the 33-item by Schutte, Malouff, Hall, Haggerty, Cooper, Golden, & Dornheim (1998) for emotional intelligence measure and 36-item of Job Satisfaction Survey by Paul E. Spector from Department of Psychology, University of South Florida (1985) for job satisfaction assess. All the data and information gathered were coded, process and analyze by using Statistical package for Social Science (SPSS) version 18.0 to produce a relevant and accurate result. Correlation statistics in findings revealed that EI was associated significantly and positively with job satisfaction. Based on the findings recommendation and suggestions for managers and organization are presented.